Assessment of effect of CYP3A inhibition, CYP induction, OATP1B inhibition, and high‐fat meal on pharmacokinetics of the JAK1 inhibitor upadacitinib - Mohamed, Mohamed‐Eslam F.; Jungerwirth, Steven; Asatryan, Armen; Jiang, Ping; Othman, Ahmed A. (British journal of clinical pharmacology, 2017)
Aims Upadacitinib (ABT‐494) is a selective Janus kinase 1 inhibitor being developed for treatment of auto‐immune inflammatory disorders. This work evaluated effects of high‐fat meal, cytochrome P450 (CYP) 3A inhibition, CYP induction, and organic anion transporting polypeptide (OATP) 1B inhibition on upadacitinib pharmacokinetics. Methods Two Phase 1 evaluations were conducted, each in 12 healthy subjects. In Study 1, using a randomized, two‐sequence crossover design, a 3 mg dose of upadacitinib (immediate‐release capsules) was administered alone under fasting conditions, after high‐fat meal, or on Day 4 of a 6‐day regimen of 400 mg once‐daily ketoconazole. In Study 2, a 12 mg upadacitinib dose was administered alone, with the first, and with the eighth dose of a 9‐day regimen of rifampin 600 mg once daily. Upadacitinib plasma concentrations were characterized. Results Administration of upadacitinib immediate‐release capsules after a high‐fat meal decreased upadacitinib Cmax by 23% and had no impact on upadacitinib AUC relative to the fasting conditions. Ketoconazole (strong CYP3A inhibitor) increased upadacitinib Cmax and AUC by 70% and 75%, respectively. Multiple doses of rifampin (broad CYP inducer) decreased upadacitinib Cmax and AUC by approximately 50% and 60%, respectively. A single dose of rifampin (also an OATP1B inhibitor) had no effect on upadacitinib AUC. Upadacitinib was well tolerated when co‐administered with ketoconazole, rifampin, or after a high‐fat meal. Conclusions Strong CYP3A inhibition and broad CYP induction result in a weak and moderate effect, respectively, on upadacitinib exposures. OATP1B inhibition and administration of upadacitinib immediate‐release formulation with food does not impact upadacitinib exposure.